2011
DOI: 10.1002/app.35157
|View full text |Cite
|
Sign up to set email alerts
|

Proton conductive reinforced poly(ethylene‐co‐styrene) membranes

Abstract: Polymers with ionic conductivity are useful materials for ion exchange membranes, separators, and electrolytes in electrochemical cells. New ionomers are currently being sought to replace the ionomers, which contain fluorine and are harmful to environment and expensive. A new and promising ionomer is a sulfonated ethylene/styrene copolymer. A nearby alternating copolymer with styrene content of 47 mol % was polymerized with metallocene/MAO catalyst. Membranes were prepared by hot-pressing copolymer films with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…Several sulfonate-based single-ion conducting ionomer systems have been developed including those based on poly(2-acrylamido-2-methyl-1-propane-sulfonate) (PAMPS) [22,25], copolymers of sulfonate polyesters [26,27], sulfonated ethylene and styrene systems [28] and styrene-ethylene and butylenestyrene systems [29,30]. Very recently, Noor et al studied a series of PAMPS-based systems containing both Na + and the methyltriethyl ammonium cation (N 1222 , where the subscript numbers indicate the number of carbon sites in each alkyl chain) [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…Several sulfonate-based single-ion conducting ionomer systems have been developed including those based on poly(2-acrylamido-2-methyl-1-propane-sulfonate) (PAMPS) [22,25], copolymers of sulfonate polyesters [26,27], sulfonated ethylene and styrene systems [28] and styrene-ethylene and butylenestyrene systems [29,30]. Very recently, Noor et al studied a series of PAMPS-based systems containing both Na + and the methyltriethyl ammonium cation (N 1222 , where the subscript numbers indicate the number of carbon sites in each alkyl chain) [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…He confirmed that short polypropylene fibers rapidly increased the mechanical strength in machine direction. Annala et al reported that the storage modulus and loss modulus of sulfonated ethylene/styrene copolymer were improved moderately after adding GF [ 23 ]. The strengthening effect of GF on composite was confined without surface modification.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous singleion conductor ionomer systems have been developed over the years; for example those based on poly(2-acrylamido-2-methyl-1-propane-sulfonic acid) (PAMPS) 11,12 and copolymers of sulfonate polyester, sulfonated ethylene/styrene and styreneethylene/butylene-styrene. [13][14][15][16][17] In general, however, the anion on the polymer backbone is somewhat basic, from which the cation does not readily dissociate, resulting in low ionic conductivity. A number of methods have been employed in an attempt to increase the ionic conductivity; for example the AMPS monomer has been copolymerized with N,N 0 -dimethylacrylamide (DMAA) to separate the ionic moieties along the backbone and thereby avoid multiple anion association to the cation.…”
Section: Introductionmentioning
confidence: 99%